Evaluation of Huddles: A Multisite Study. Issue 3 (July 2017) - Melton, Leslie; Lengerich, Alex; Collins, Melanie; McKeehan, Rita; Dunn, Denise; Griggs, Phyllis; Davies, Theodore; Johnson, Brenda; Bugajski, Andrew
Abstract : Regular, interdisciplinary group meetings, "huddles, " may be useful in improving communication among disciplines, resolving problems, and sharing information. Daily use of huddles may contribute to the development of a highly reliable health care organization. The purpose of this study was to describe safety huddles in relation to (1) problem type, (2) timeliness of resolution, (3) attendance of representatives from each discipline, (4) amount of information sharing, and (5) attendees' satisfaction with the process. Overall, results demonstrated that the primary function of huddles was the exchange of information that posed or had the potential to pose safety risks to patients. Across seven hospitals, the range of information sharing during huddles was 61.0% to 95.6%. Regarding satisfaction with the huddle process, staff reported that huddles were useful in improving awareness of safety concerns and also improved communication between disciplines. Huddles provide a structured format in which staff can positively impact safety concerns, form a greater sense of medical community, increase sharing of information between disciplines, quickly resolve discipline-based problems, and increase awareness of safety concerns. Given the results of this study, it is recommended that health care administrators and managers develop a huddle process.